2009
DOI: 10.1063/1.3080161
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform microwave spectroscopy of monobromogermylene (HGeBr and DGeBr), a heavy atom carbene analog

Abstract: Eight isotopologues of HGeBr and nine of DGeBr have been studied in natural abundance by pulsed-jet Fourier transform microwave spectroscopy. The reactive germylene species were produced in an electric discharge at the exit of a pulsed molecular beam valve using precursor mixtures of H(3)GeBr or D(3)GeBr in high pressure neon. In the 5-25 GHz operating range of the spectrometer, only a-type transitions were observed; K = 0 transitions for HGeBr and K = 0 and 1 transitions for DGeBr. From the observed transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…(7), are, of course, products of the field gradients at the nucleus and the quadrupole tensor elements at that nucleus.…”
Section: The Hyperfine Hamiltonian For Quadrupolar Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…(7), are, of course, products of the field gradients at the nucleus and the quadrupole tensor elements at that nucleus.…”
Section: The Hyperfine Hamiltonian For Quadrupolar Nucleimentioning
confidence: 99%
“…Also, I wished to do this in a fashion in which the mathematics was transparent. This method was first presented in a recent paper on HGeBr [7]. Since then, I have talked about my formulation of the Townes-Dailey model at spectroscopy symposia [8], and members of the audience have suggested that I should submit the model in a stand-alone manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…BN Cyclohexene has remained elusive without previous characterization because as a simple non-sterically encumbered aminoborane, 10 it is prone to dimerization or oligomerization in solution, consistent with the formation of the trimerT as the ultimate decomposition product. In this work, we describe the gas phase microwave spectroscopy characterization of BN Cyclohexene, which is produced from BN cyclohexane under microwave spectroscopy measurement conditions (i.e., heating sample in a Ne gas stream prior to insertion into the microwave cavity) This process is illustrated in the lower portion of Scheme 12 Interpretation of the nuclear quadupole coupling strengthsusing the extended Townes-Daily analysis 13 provided additional information regarding the aromaticity. The nitrogeneQqcomponent parallel to the c-axis for is consistent with other nitrogen-containing aromatic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental determination of the nuclear quadrupole coupling constants for 14 N, 11 B, and 10 B allows the determination of the valence p-orbital electron occupation on those atoms from the Townes-Daily model. 11 It is of interest to compare the latter with the calculated natural bond orbital occupation for boron and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental determination of the nuclear quadrupole coupling constants for 14 N, 11 B, and 10 B allows the determination of the valence p-orbital electron occupation on those atoms from the Townes-Daily model. 11 It is of interest to compare the latter with the calculated natural bond orbital occupation for boron and nitrogen. The experimental molecular parameters and the π-electron occupancies on boron and nitrogen can provide additional information regarding the aromaticity for 1,2-dihydro-1,2-azaborine.…”
Section: Introductionmentioning
confidence: 99%